Paradigm Lost: Ocean Acidification Will Overturn the Concept of Larval-Fish Biophysical Dispersal - Leis, Jeffrey M. (Frontiers in Marine Science, 2018)
Most marine ecologists have in the past 25 years changed from supporting a passive-dispersal paradigm for larval marine fishes to supporting a biophysical-dispersal paradigm wherein the behaviour of larvae plays a central role. Research shows larvae of demersal perciform fishes have considerable swimming and orientation abilities over a major portion of their pelagic larval duration. These abilities depend on sensory function, and some recent research has indicated anthropogenic acidification of the oceans will by the end of the century result in sensory dysfunction. This could strongly alter the ability of fish larvae to orientate in the pelagic environment, to locate suitable settlement habitat, to bet-hedge, and to colonize new locations. This paper evaluates the available publications on the effects of acidification on senses and behaviours relevant to dispersal of fish early life-history stages. A large majority of studies tested CO2 values predicted for the middle to end of the century. Larvae of fourteen families—all but two perciform—were studied. However, half of studies used Damselfishes (Pomacentridae), and except for swimming, most studies used settlement-stage larvae or later stages. In spite of these taxonomic and ontogenetic restrictions, all but two studies on sensory function (chemosensation, hearing, vision, detection of estuarine cues) found deleterious effects from acidification. The four studies on lateralization and settlement timing all found deleterious effects from acidification. No clear effect of acidification on swimming ability was found. If fish larvae cannot orientate due to sensory dysfunction, their dispersal will, in effect, conform to the passive dispersal paradigm. Modelling incorporating larval behaviour derived from empirical studies indicates that relative to active larvae, passive larvae will have less self-recruitment, higher median and mean dispersal distances, and lower settlement rates: further, bet hedging and colonization of new locations will decrease. The biophysical dispersal paradigm will be lost in theory and in fact, which is predicted to result in lower recruitment and less bet hedging for demersal, perciform fishes. More research is required to determine if the larvae of other Orders will be effected in the same way, or if warm- and cold-water fish faunas will be similarly effected.